Influence of a single defect on the conductance of a tunnel point contact between a normal metal and a superconductor: Электpонные свойства металлов и сплавов - Avotina, Ye.S.; Kolesnichenko, Yu.A.; Ruitenbeek, J.M. van (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We have investigated theoretically the conductance of a normal–superconductor point contact in the tunnel limit and analyzed the quantum interference effects originating from the scattering of quasi-particles by point-like defects. Analytical expressions for the oscillatory dependence of the conductance on the position of the defect are obtained for the defect situated either in the normal metal, or in the superconductor. It is found that the amplitude of oscillations significantly increases when the applied bias approaches the gap energy of the superconductor. The spatial distribution of the order parameter near the surface in the presence of a defect is also obtained.